Accesibilidad viaria y desarrollo territorial en la España peninsular: una propuesta de análisis - Nastagi Mattoni, Nicoletta (Geographicalia, 2016)
This study analyzes the more significant aspects of the development of the Spanish road network, giving emphasis to the recent evolution. In particular, it offers an analysis of the relationship that appears between the development of the various Spanish networks and the development of the social economy of the territory within the same network developments. This proposal is articolated through the quantifing of the concept of accessibility and on the eventual association of the demografic expansivness
Keywords: Spain; road network; accessibility.